Innovative Method of Developing Professional Ideas of High School Students - V. Zholudeva, Svetlana; N. Ulybysheva, Irina (International Journal of Psychosocial Rehabilitation, 2020)
The paper presents data on the features of professional ideas of high school students. The specific characteristics of professional ideas are revealed in interaction with professional orientations of a personality. In the authors’ opinion, researching the professional ideas of high school students is an indispensable condition for forming adequate self-determination and choice of profession in accordance with the personal components of an individual. The authors thoroughly selected the methodological tools and designed an innovative program aimed at developing, actualizing, and correcting the professional ideas of high school students. As a result of the research and analysis of data, the authors identified the features of professional ideas of high school students and revealed the qualitative specificity of the characteristics of professional ideas of high school students in interaction with various professional orientations of a personality. It is marked that the obtained results can be used to increase the efficiency of the educational process. The conclusion is made that there is qualitative specificity in the professional ideas of high school students belonging to various groups of professional orientation.